2016
DOI: 10.1016/j.jaci.2016.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Pathways through which asthma risk factors contribute to asthma severity in inner-city children

Abstract: Background Pathway analyses can be used to determine how host and environmental factors contribute to asthma severity. Objective Investigate pathways explaining asthma severity in inner-city children. Methods Based on medical evidence in the published literature, we developed a conceptual model to describe how eight risk-factor domains (allergen sensitization, allergic inflammation, pulmonary physiology, stress, obesity, vitamin D, environmental tobacco smoke (ETS) exposure and rhinitis severity) are linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 30 publications
2
50
0
1
Order By: Relevance
“…The Inner-City Asthma Consortium - Asthma Phenotypes in the Inner City (APIC) study contributed to understanding the role of host and environmental factors influencing severity of asthma among inner-city children and adolescents in the US ●●[18,19]. Results of this study revealed that, in spite of good adherence to optimal treatment, inner-city children and adolescents with difficult-to-control asthma had little improvement in symptoms, exacerbations, and pulmonary physiology over a one-year follow-up.…”
Section: Cockroach Allergy and Inner-city Asthmamentioning
confidence: 99%
See 1 more Smart Citation
“…The Inner-City Asthma Consortium - Asthma Phenotypes in the Inner City (APIC) study contributed to understanding the role of host and environmental factors influencing severity of asthma among inner-city children and adolescents in the US ●●[18,19]. Results of this study revealed that, in spite of good adherence to optimal treatment, inner-city children and adolescents with difficult-to-control asthma had little improvement in symptoms, exacerbations, and pulmonary physiology over a one-year follow-up.…”
Section: Cockroach Allergy and Inner-city Asthmamentioning
confidence: 99%
“…Allergen sensitization, allergic inflammation, pulmonary physiology, environmental tobacco smoke (ETS) exposure, and rhinitis severity were significantly related to asthma severity, whereas stress, obesity, and vitamin D showed no significant effect on disease severity ●●[18]. Allergen sensitization was the strongest association detected (linked to allergic inflammation, and subsequently to pulmonary physiology and rhinitis severity) to contribute to asthma severity, suggesting that allergen sensitization could be the originating domain among the multiple pathways involved in severity of the disease ●●[18]. …”
Section: Cockroach Allergy and Inner-city Asthmamentioning
confidence: 99%
“…The APIC study 5-7 was an observational study designed to identify determinants of asthma severity. During the APIC study, children ages 6 to 17 years, with a wide range of asthma severity, received standardized guidelines-directed asthma treatment for one year.…”
Section: To the Editormentioning
confidence: 99%
“…Thus, recognition of the amount of allergic inflammation in an inner-city child may not only assist in guiding allergen avoidance strategies, but may also predict children in need of closer monitoring due to difficult- to-control asthma. Finally, Lui et al(71) investigated pathways through which asthma risk factors contribute to asthma severity in these inner-city children. In this analysis, it was discovered that the allergy pathway and tobacco smoke exposure pathway exerted the predominant effects on asthma severity.…”
Section: Asthma and The Environmentmentioning
confidence: 99%
“…In the APIC study, environmental tobacco smoke was associated with worsening pulmonary physiology and increased asthma severity. (71) Horner et al(73) reported that increased child-reported stress during the day was associated with an increased likelihood of awakening that night from asthma, but not awakening for a reason other than asthma. Finally, a study of inner-city schools discovered that increased exposures to mouse allergen in the schools was associated with increased asthma symptom days and decreased lung function.…”
Section: Asthma and The Environmentmentioning
confidence: 99%